Investigating the Metabolome of Schistosoma mansoni by High-Resolution Mass Spectrometry Imaging - Kadesch, Patrik; Justus Liebig University Giessen (My University, 2021)
Neglected tropical diseases (NTD) are a burden to one billion humans in the (sub-)tropics and poverty-related regions, worldwide. Schistosomiasis, caused by the parasitic flatworm Schistosoma mansoni, is one of those NTDs. The disease is currently spreading because of climate change and migration, exposing approximately 700 million people to the risk of infection. Therefore, novel strategies are required to prevent infection and to eliminate the worm burden. One promising drug target is the surface (tegument) of adult male and female schistosome worms. Schistosomes live in constant pairing contact, established via the teguments of male and female, as a prerequisite for egg production. Living in the blood stream, they are also in contact with the host’s immune system and therefore require immune evasion, moderated by the outer tegument. Lipids are one major class of constituents of the tegument, but limited information is available on its exact biochemical composition. The abundance and spatial distribution of lipids is therefore of high interest. MS is the technique of choice to answer this research question, as it allows multiplexed lipid detection in a nontargeted analysis approach. AP-SMALDI MSI is capable of delivering high spatial resolution in the micrometer range. Due to the small size of Schistosoma (approximately 500 μm in length), this high lateral resolution is essential to resolve detailed structures within the worms. In addition, this technique requires low sample quantities, and recent instrumental advances enable analysis of 3D-surfaces. We utilized MSI to investigate and characterize the spatial distribution of lipids on the surface of adult schistosome worms in comparison to their inner tissue. However, there are no suitable protocols available for production of the necessary cryosections and analysis by MSI. To overcome this limitation, different embedding protocols, like the classical embedding in cryomolds were tested and modified, e.g. by centrifugation steps for improved planarity. However, embedded worms were lacking planar orientation and sections were not intact after cutting. Also, the tissue was partially disrupted during this process, leading to poor section quality. Finally, a microembedding approach was developed, which uses small quantities of gelatin and represents a high-precision approach. This protocol allowed preparing consecutive high-quality cryosections of a mating worm couple. MS ion images of intact couples revealed differences between male and female in metabolites and lipids. Detailed structures observed from light microscopic images were retained in ion images at 10 μm and 5 μm spatial resolution. To further investigate putative isobaric interferences, on-tissue tandem mass spectrometry imaging (MS2I) was utilized to trace characteristic lipid fragments across the tissue and to demonstrate the high sensitivity of the setup even at a lateral resolution < 10 μm. This work was summarized in publication one and enabled the investigation of surface in comparison to the inner tissue of schistosomes. High-resolution MSI of male and female surfaces and couple sections was conducted. An LC-MS/MS-based data repository in combination with unsupervised ion image annotation using the “Metaspace” software was employed for lipid assignment. Multivariate statistical analysis of MSI data by hierarchical clustering revealed deviating signal intensities of lipids on surface vs inner tissue of the worm. PC and specific PE signals were enhanced inside the worm, while SM, PS, LPC and other PE lipids were more abundant on the surface. These findings were in accordance with literature, but enhanced the compositional information from lipid class level to lipid species level. In addition, for PEs, the number of carbon atoms in the fatty acyl chains was found to be decreased on the surface in comparison to the inner tissue. Differences between male and female surface compositions were observed as well. Several sex-specific TGs were found, which differed in numbers of fatty acid carbon atoms and double bonds. For the first time, differences in lipid composition were found between male and female S. mansoni worms. Now a broad toolbox of preparative and data interpretation workflows is available to the scientific community, adaptable to a variety of research issues.
Keywords: ddc:540